STRATEGI KEMENTERIAN AGAMA DALAM MENEKAN PENYEBARAN PAHAM RADIKALISME AGAMA DI LINGKUP PENDIDIKAN MADRASAH ‘ALIYAH KABUPATEN BANDUNG - Rendy Adiwilaga; Nia Tresnawati Muchtar; , Mustabsyirotul Ummah Mustofa (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This research is motivated by the rampant phenomenon of religious radicalism movements in educational institutions, especially religious educational institutions as the realm of education that is most vulnerable to being infiltrated by religious radicalism movements. These expressions can be seen from the prohibition of flag salute, ceremonies as acts that rest and so on that arise from the dynamics of extracurricular organisations. This research captures the Ministry of Religious Affairs' strategy in dealing with the spread of radicalism in the Madrasah Aliyah schools in the Bandung Regency. The results show that in the aspect of determining goals and objectives, the Bandung Regency Ministry of Religious Affairs, as stated in its vision, has the aim of suppressing the spread of radicalism and spreading moderation in religion, both to students and the community. In terms of policy formulation, or other words, programmes, the Ministry of Religious Affairs of Bandung Regency, together with madrasahs such as Aliyah in its working area, set three important strategies for suppressing the spread of radicalism. The first is the cultivation of the value of religious moderation, then the formation of an anti-radicalism cyber team coupled with an anti-drug cyber team, and finally a comprehensive consolidation by involving various religious organizations, religious leaders, and related parties in its efforts to suppress the Islamic radicalism movement in the education environment; Finally, related to operationalisation, unfortunately only the religious moderation program is intensely implemented, namely through technical guidance to teachers and seminars conducted for students. In addition, there is training in curriculum formulation through insertion material to counteract radicalism.